Effect of temperature and anion on densities, viscosities, and refractive indices of 1-Octyl-3-propanenitrile Imidazolium-based ionic liquids - Ziyada, A.K. (American Chemical Society, 2014)
A series of 1-octyl-3-propanenitrile imidazolium based room temperature ionic liquids incorporated with different sulfonate-based anions were synthesized and characterized using 1H NMR, Fourier transform infrared spectroscopy (FTIR), and elemental analysis. The density and viscosity were measured at T = (293.15 to 353.15) K, the refractive index was measured at T = (298.15 to 383.15) K, and the thermal expansion coefficient was estimated from the density values. The effects of the anions on these physical properties and on the lattice energy were discussed. Â© 2014 American Chemical Society.